Sosialisasi Profesi Arsitek sebagai Upaya Penguatan Pemahaman Regulasi dan Etika Profesi bagi Generasi Calon Arsitek - Rizqiyah, Umara Hasmarani; Husnirrahman J; Firnawati Firnawati; Armiwaty Armiwaty; Idrus, Raeny Tenriola (FKIP, Universitas Palangka Raya, 2026)
This community service activity aims to enhance the understanding of high school graduates regarding the architect profession, educational pathways, and the legal requirements needed to become a professional architect according to the guidelines of the Indonesian Institute of Architects (IAI). The socialization event was held online on November 27, 2025, featuring two professional IAI architects as speakers and attended by 97 participants. The activity included interactive material presentations, discussions, and evaluations through a pretest and post-test consisting of five questions. The results showed an increase in participants' understanding of the role, responsibilities, and legal aspects of the profession, with an average correct answer rate of over 90%. The most significant improvement occurred in the legal aspects, where participants gained a better understanding of the importance of the Architect Registration Certificate (STRA) as legal proof of professional competence. This socialization proved effective in raising awareness among prospective students about the importance of professionalism, ethics, and regulatory knowledge in architectural practice. The event also served as an academic promotion tool that strengthened the connection between architectural education and society's need for architects with integrity.